1996
DOI: 10.1056/nejm199601113340204
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in the Families of Patients with Adenomatous Polyps

Abstract: Siblings and parents of patients with adenomatous polyps are at increased risk for colorectal cancer, particularly when the adenoma is diagnosed before the age of 60 or--in the case of siblings--when a parent has had colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
25

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(141 citation statements)
references
References 28 publications
9
107
0
25
Order By: Relevance
“…Previous studies have found pelvic irradiation to be a risk factor for colorectal cancer in both men and women [13][14]. Several studies support the association of a positive family history of colorectal cancer and increased risk for neoplasia [15][16][17][18][19]. In our study, having a first degree relative with CRC increased the risk for advanced neoplasia, while having a second degree relative showed a trend toward increased risk.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have found pelvic irradiation to be a risk factor for colorectal cancer in both men and women [13][14]. Several studies support the association of a positive family history of colorectal cancer and increased risk for neoplasia [15][16][17][18][19]. In our study, having a first degree relative with CRC increased the risk for advanced neoplasia, while having a second degree relative showed a trend toward increased risk.…”
Section: Discussionsupporting
confidence: 79%
“…Verwandte zweiten Grades (Großeltern, Geschwister der Eltern, Enkel) von Patienten mit kolorektalen Karzinomen haben ein leicht erhöhtes Karzinomrisiko (RR 1,5); dieses ist aber derzeit nur unzureichend untersucht und bisher nicht in der Praxis verifiziert [189,192,193,203,204] Evidenz aus Aktualisierungsrecherche: [190, 193, 205 -208] Konsens Hintergrund Das Risiko dieser Verwandten, ein KRK zu entwickeln, ist im Mittel etwa 2-fach gegenüber der Allgemeinbevölkerung gesteigert [190, 193, 205 -208]; es besteht ein 80 % höheres Risiko bei Eltern und Geschwistern von Adenom-Patienten im Vergleich mit deren Lebenspartnern [205]. Auch hier ist die Risikohöhe vom Alter des Indexpatienten abhängig: Ist dieser jünger als 60 Jahre, ist das mittlere Risiko nur leicht erhöht, ist er jünger als 50 Jahre, ist das Risiko ca.…”
Section: Level Of Evidence 2bunclassified
“…If two first-degree relatives have colorectal cancer or a single first-degree relative is diagnosed at an age less than 50 years, the risk increases to 3-fold or even greater. There is some increased risk even when second-or third-degree relatives have colon cancer, or a first-degree relative has a colonic adenomatous polyp [5,6]. Finally, age of diagnosis also influences the degree of risk.…”
Section: Common Familial Risk Of Colon Cancermentioning
confidence: 99%